Capnocytophaga in the dental plaque of immunocompromised children with cancer - J. L. SIXOU, A. AUBRY-LEULIETTE, O. DE MEDEIROS-BATTISTA, S. LEJEUNE, A. JOLIVET-GOUGEON, H. SOLHI-P (Paediatric Dentistry, 2006)
Capnocytophaga species are gram-negative, capnophilic, gliding bacilli. They are members of the oral commensal flora. Supra- and subgingival plaque represent their main reservoirs [1–3].